Clinical significance of DNA methylation in chronic lymphocytic leukemia patients: results from 3 UK clinical trials - Wojdacz, Tomasz K.; Amarasinghe, Harindra E.; Kadalayil, Latha; Beattie, Alice; Forster, Jade; Blakemore, Stuart J.; Parker, Helen; Bryant, Dean; Larrayoz, Marta; Clifford, Ruth; Robbe, Pauline; Davis, Zadie A.; et al. (Blood advances, 2019)
Chronic lymphocytic leukemia patients with mutated immunoglobulin heavy-chain genes (IGHV-M), particularly those lacking poor-risk genomic lesions, often respond well to chemoimmunotherapy (CIT). DNA methylation profiling can subdivide early-stage patients into naive B-cell–like CLL (n-CLL), memory B-cell–like CLL (m-CLL), and intermediate CLL (i-CLL), with differing times to first treatment and overall survival. However, whether DNA methylation can identify patients destined to respond favorably to CIT has not been ascertained. We classified treatment-naive patients (n = 605) from 3 UK chemo and CIT clinical trials into the 3 epigenetic subgroups, using pyrosequencing and microarray analysis, and performed expansive survival analysis. The n-CLL, i-CLL, and m-CLL signatures were found in 80% (n = 245/305), 17% (53/305), and 2% (7/305) of IGHV-unmutated (IGHV-U) cases, respectively, and in 9%, (19/216), 50% (108/216), and 41% (89/216) of IGHV-M cases, respectively. Multivariate Cox proportional analysis identified m-CLL as an independent prognostic factor for overall survival (hazard ratio [HR], 0.46; 95% confidence interval [CI], 0.24-0.87; P = .018) in CLL4, and for progression-free survival (HR, 0.25; 95% CI, 0.10-0.57; P = .002) in ARCTIC and ADMIRE patients. The analysis of epigenetic subgroups in patients entered into 3 first-line UK CLL trials identifies m-CLL as an independent marker of prolonged survival and may aid in the identification of patients destined to demonstrate prolonged survival after CIT. •DNA methylation signatures can be used to divide IGHV-mutated CLL into clinically relevant subgroups.•The memory-like DNA methylation subgroup is an independent marker of prolonged survival for patients treated with chemoimmunotherapy. [Display omitted]